“We got to know each other better and talked more about stuff we usually kind of do not talk about.” A qualitative study of the acceptability of the Norwegian version of the Identity Project - Oppedal, Brit; Türken, Salman; Ali, Warsame A.; Adem, Hayat Abdu (Frontiers in Education, 2025)
IntroductionEvidence is emerging in Europe of the efficiency of culturally adapted versions of the Identity Project (IP), a U.S.-developed school-based universal mental health promoting intervention. However, in depth research knowledge about the IP’s user acceptability among school staff and students is lacking. User acceptability is an important factor in ensuring a successful implementation and large-scale uptake of effective interventions in educational institutions.MethodsThe present study explored interview data from teachers and diversity counselors (deliverers; n = 10) and upper secondary school students (receivers; n = 16) of the intervention in Norwegian secondary schools to get information about which aspects of the IP may enhance or reduce its acceptability. We used thematic analysis to generate themes.ResultsThree themes indicated positive changes resulting from the IP. These themes revealed that the most prominent aspects of acceptability were related to the users’ perception that they got to know each other in new ways through working together on topics about their ethnicity and culture (more culturally inclusive classrooms), that the curriculum was engaging and provided important language to describe the students’ minoritizing experiences (expanding one’s perspectives), and to the effect the curriculum had on the users’ ethnic-cultural identity exploration (coming to terms with ethnic-cultural identity). A fourth theme (challenging concepts) involved aspects that might lower acceptability, and suggested revisions needed to ensure successful future implementation of the intervention.DiscussionThe main aspect of the IP making it acceptable to deliverers and receivers is that the curriculum provides them with a safe space, and much needed strategies and tools to engage in discussions about their ethnicity and culture in the classroom. In conclusion, the user acceptability of the IP is strong and demonstrates that the curriculum has a potential of larger-scale implementation into educational institutions’ multicultural education strategy.